Incidence and risk factors of preoperative isolated calf deep venous thrombosis following hip fractures. Issue 12 (25th March 2022) - Zhao, Weiguang; Zhao, Jianlong; Liu, Tiantian; Liu, Zhenwu; Liu, Li
Abstract : Abstract: There is still a lack of data on isolated calf deep vein thrombosis (ICDVT) following hip fractures surgery. The study aimed to determine the incidence of preoperative ICDVT and the associated risk factors in patients with hip fractures requiring surgery. The 289 patients who required hip surgery were included, duplex ultrasonography was routinely used to make a definite diagnosis of preoperative ICDVT located in unilateral or bilateral calf. Data on demographics and laboratory-associated blood biomarkers results were included. Univariate analyses were used to analyse the data of demographics, comorbidities, personal history operation related indexes and laboratory biomarkers, then the multivariate logistic regression analysis was employed to identify the independent risk factors associated with ICDVT. Sixty-eight (23.5%) patients were diagnosed with preoperative ICDVTs. The univariate analyses showed significant differences regarding ICDVT were age, current smoking, alcohol consumption, time from injury to operation, albumin, white blood cells, lymphocyte, red blood cells, hemoglobin, hematocrit, and activated partial thromboplastin time level among the 44 factors. The multivariable model confirmed 3 risk factors were significantly independent in association with preoperative ICDVTs, including current smoking, time delay from injury to operation and activated partial thromboplastin time ( < 28seconds). The incidence of preoperative ICDVT in hip fracture was 23.5%, and patients with associated risk factors are prone to form ICDVTs, identification of these factors may help to reduce the incidence of ICDVT with hip fractures by taking early prevention measures.